Patient hopes for diagnostic genomic sequencing: roles of uncertainty and social status - Khan, Cynthia M (Eur J Hum Genet, 2016)
For patients with unexplained or undiagnosed conditions, genomic sequencing offers the hope of resolving unanswered questions. With the growth of clinical genomic sequencing, understanding factors that shape patients' hope for information could have important implications for developing patient education guidelines. Based on the goal-directed theory of hope, we investigated illness uncertainty as a form of motivation and subjective social status as a form of perceived resources to predict the amount and kinds of information that adult patients (N=191) and parents of pediatric patients (N=79) hoped to receive from diagnostic sequencing results. Participants were part of a larger longitudinal study on clinical genomic sequencing, but the current study focuses on their hopes for diagnostic sequencing results. Hopes for information were assessed through close-ended and open-ended responses. Findings from mixed methods analyses indicated that although patients and parents hoped to learn multiple kinds of information from diagnostic sequencing results, their hopes appeared to be influenced by their illness uncertainty and perceptions of their social and economic resources. These findings suggest that patients' illness uncertainty and perceived resources could be useful avenues for discussing patient hopes and educating patients about strengths and limitations of genomic sequencing.